Polymer chemistry - Royal Society of Chemistry (Great Britain) (Royal Society of Chemistry, 2010)
A peer-reviewed journal publishing advances in polymer chemistry encompassing all aspects of synthetic and biological macromolecules, and related emerging areas.
Keywords: Polymers : Periodicals; Macromolecules : Periodicals; Polymerization : Periodicals; Macromolecules; Polymerization; Polymers